Spreader graft fixation through a closed rhinoplasty approach: descriptive study and preliminary clinical experience - Eman Hamdy; Fedaey Habaza; Hossam Elsisi (The Egyptian Journal of Otolaryngology)
Abstract Introduction The use of either an open or closed approach in rhinoplasty has been a topic of debate. Widening the narrow internal nasal valve area through internal nasal valve augmentation presents a strong case for an open approach. However, this study presents a direct method for fixing spreader grafts using a closed approach, which offers the benefits of precise placement and stability without an external scar. Materials and methods Nine patients with functional and/or cosmetic complaints that need spreader grafts insertion were enrolled in the study. Spreader grafts placed and fixed by stitches using a closed rhinoplasty approach with additional esthetic steps added as necessary. Results Valve collapse was secondary in 2 cases, and the spreader graft was inserted bilaterally in all but one patient. Their complaint was either functional (44%), cosmetic (22%), or both (33%). NOSE scores showed improvement in all patients with a mean operative time was (68.68 ± 12.45 SD) minutes and postoperative complications were acceptably low. Conclusion In this report, we describe fixation of spreader graft through a closed technique with visualization of the entire septal cartilage frame. This method combines the advantages of direct manipulation and fixation with all the benefits of a closed approach.